The motivation of business leaders in socialist and market-based systems (An essay to celebrate the 90th birthday of János Kornai) - Mihályi, Peter (Economics and Business Review, 2017)
Janos Kornai was well ahead of mainstream economic thought in comprehending that senior executives have been operating in an intrinsically contradictory situation both in socialist and market-based economies and that there is no full remedy to handle conflicts of interest which arise. Kornai presented a comprehensive theory on this in his most important book, the Anti-Equilibrium, as early as 1971. The difficulties experienced by state-owned enterprises (SOEs) were not rooted merely in the socialist ownership form, but they were, to a significant extent, caused by the fact that SOEs were typically very large firms.